Evaluation of sexual function and vaginal prolapse after radical cystectomy in women: a study to explore an under-evaluated problem - Wenk, Maren; Westhoff, Niklas Christian; Liedl, Bernhard; Michel, Maurice Stephan; Grüne, Britta; Kriegmair, Maximilian (International urogynecology journal, 2023)
The objective was to evaluate sexual function, vaginal prolapse, and quality of life (QoL) in women after radical cystectomy (RC) using validated questionnaires and pelvic organ prolapse quantification (POP-Q) measurement.